Забезпечення економічної безпеки територіального розвитку в умовах ризиків і загроз - Перепелюкова, О. В. (ХНУРЕ, 2025)
The peculiarities of the territorial development of the state under conditions of military aggression have been studied. Priority tasks at the level of territorial communities have been determined to ensure the competitiveness of territories. It has been established that territorial development is the basis for the stability of the state's development. Measures to improve the economic condition of territories and the state as a whole have been identified. The importance of taking into account the peculiarities of territorial development when forming strategies and plans for the general development of the state has been substantiated.
Keywords: економічна безпека; територіальний розвиток